Những câu hỏi liên quan
Vũ Thảo Anh
Xem chi tiết
Phan Ánh Dương
Xem chi tiết
Nguyễn đăng long
14 tháng 12 2020 lúc 21:48

6x^2-(x-3)(3x+2)-6

=6x^2-6x^2+x-9x-6-6

=-5x-12

Bình luận (0)
Thùy Linh
14 tháng 12 2020 lúc 22:10

undefined

Bình luận (0)
Hoàng Huy
Xem chi tiết
Nguyễn Lê Phước Thịnh
28 tháng 7 2021 lúc 22:29

a) Ta có: \(\dfrac{x}{x-3}-\dfrac{6}{x}-\dfrac{9}{x^2-3x}\)

\(=\dfrac{x^2}{x\left(x-3\right)}-\dfrac{6\left(x-3\right)}{x\left(x-3\right)}-\dfrac{9}{x\left(x-3\right)}\)

\(=\dfrac{x^2-6x+18-9}{x\left(x-3\right)}\)

\(=\dfrac{\left(x-3\right)^2}{x\left(x-3\right)}=\dfrac{x-3}{x}\)

b) Ta có: \(\dfrac{7}{x}-\dfrac{x}{x+6}+\dfrac{36}{x^2+6x}\)

\(=\dfrac{7\left(x+6\right)-x^2+36}{x\left(x+6\right)}\)

\(=\dfrac{7x+42-x^2+36}{x\left(x+6\right)}\)

\(=\dfrac{-\left(x^2-7x-78\right)}{x\left(x+6\right)}\)

\(=\dfrac{-\left(x^2-13x+6x-78\right)}{x\left(x+6\right)}\)

\(=\dfrac{-\left[x\left(x-13\right)+6\left(x-13\right)\right]}{x\left(x+6\right)}\)

\(=\dfrac{13-x}{x}\)

c) Ta có: \(\dfrac{6}{x-3}-\dfrac{2x-6}{x^2-9}-\dfrac{4}{x+3}\)

\(=\dfrac{6\left(x+3\right)-2x+6-4\left(x-3\right)}{\left(x-3\right)\left(x+3\right)}\)

\(=\dfrac{6x+18-2x+6-4x+12}{\left(x-3\right)\left(x+3\right)}=\dfrac{36}{\left(x-3\right)\left(x+3\right)}\)

Bình luận (0)
lan vo
Xem chi tiết
Nguyễn Hoàng Minh
11 tháng 11 2021 lúc 14:40

\(=\dfrac{-3\left(x-1\right)}{\left(1+x\right)^2}\cdot\dfrac{x+1}{6\left(x-1\right)\left(x+1\right)}\left(x\ne\pm1\right)\\ =\dfrac{-1}{2\left(x+1\right)^2}\)

Bình luận (0)
Thư Phạm
Xem chi tiết
Lấp La Lấp Lánh
22 tháng 8 2021 lúc 11:36

\(\left(x-6\right)\left(x+6\right)-2x\left(x+6\right)+\left(x+6\right)^2=x^2-36-2x^2-12x+x^2+12x+36=0\)

Bình luận (0)
Nguyễn Lê Phước Thịnh
22 tháng 8 2021 lúc 13:27

Ta có: \(\left(x-6\right)\left(x+6\right)-2x\left(x+6\right)+\left(x+6\right)^2\)

\(=x^2-36-2x^2-12x+x^2+12x+36\)

=0

Bình luận (0)
ko có tên
Xem chi tiết
ILoveMath
5 tháng 1 2022 lúc 22:29

\(\dfrac{3-6x}{x^2-1}:\dfrac{1-x}{2x-1}\\ =\dfrac{3\left(1-2x\right)}{\left(x-1\right)\left(x+1\right)}.\dfrac{1-2x}{x-1}\\=\dfrac{3\left(1-2x\right)^2}{\left(x-1\right)^2\left(x+1\right)} \)

Bình luận (0)
Nhung Nguyen
Xem chi tiết
Nguyễn Lê Phước Thịnh
7 tháng 1 2022 lúc 9:18

Bài 1: 

b: \(=\dfrac{x+3-4-x}{x-2}=\dfrac{-1}{x-2}\)

Bài 2: 

a: \(=\dfrac{x+1}{2\left(x+3\right)}+\dfrac{2x+3}{x\left(x+3\right)}\)

\(=\dfrac{x^2+x+4x+6}{2x\left(x+3\right)}=\dfrac{x^2+5x+6}{2x\left(x+3\right)}=\dfrac{x+2}{2x}\)

d: \(=\dfrac{3}{2x^2y}+\dfrac{5}{xy^2}+\dfrac{x}{y^3}\)

\(=\dfrac{3y^2+10xy+2x^3}{2x^2y^3}\)

e: \(=\dfrac{x^2+2xy+x^2-2xy-4xy}{\left(x+2y\right)\left(x-2y\right)}=\dfrac{2x^2-4xy}{\left(x+2y\right)\cdot\left(x-2y\right)}=\dfrac{2x}{x+2y}\)

Bình luận (0)
Ngọc tấn đoàn
Xem chi tiết
Nguyễn Lê Phước Thịnh
27 tháng 12 2021 lúc 20:24

\(=4x^2-12x+9-4x^2+13x-2x=-x+9\)

Bình luận (0)
Nguyễn Thị Minh Thu
27 tháng 12 2021 lúc 20:33

\(= 4x^2 - 12x + 9 - 4x^2 + 13x - 2x = -x + 9\)

Bình luận (2)
PHK27
Xem chi tiết
Tô Mì
19 tháng 1 2022 lúc 10:44

a. \(3x\left(2x+1\right)=6x^2+3x\)

b. \(\left(12x^3-18x^2+6x\right):6x=2x^2-3x+1\)

 

c. \(\dfrac{7x+6}{5x-1}+\dfrac{8x-9}{5x-1}=\dfrac{15x-3}{5x-1}=\dfrac{3\left(5x-1\right)}{5x-1}=3\)

Bình luận (0)
๖ۣۜHả๖ۣۜI
19 tháng 1 2022 lúc 10:44

\(a.3x\left(2x+1\right)\\ =6x^2+3x\)

\(b.\left(12x^3-18x^2+6x\right):6x\\ =2x^2-3x+1\)

\(c.\dfrac{7x+6}{5x-1}+\dfrac{8x-9}{5x-1}=\dfrac{7x+6+8x-9}{5x-1}=\dfrac{15x-3}{5x-1}=\dfrac{3\left(5x-1\right)}{5x-1}=3\)

Bình luận (0)
ttanjjiro kamado
19 tháng 1 2022 lúc 10:48

a. 3x(2x+1)=6x2+3x3x(2x+1)=6x2+3x

b. (12x3−18x2+6x):6x=2x2−3x+1

c. \(\dfrac{7x+6}{5x-1}+\dfrac{8x-9}{5x-1}=\dfrac{15x-3}{5x-1}=\dfrac{3\left(5x-1\right)}{5x-1}=3\)

Bình luận (0)